Adeno-associated virus serotype 9 efficiently targets ischemic skeletal muscle following systemic delivery - Katwal, Arabindra B. (2013)
Targeting therapeutic gene expression to skeletal muscle following intravenous administration is an attractive strategy for treating peripheral arterial disease (PAD), except that vector access to the ischemic limb could be a limiting factor. Since AAV serotype 9 transduces skeletal muscle at high efficiency following systemic delivery, we employed AAV-9 vectors bearing luciferase or enhanced green fluorescent protein (eGFP) reporter genes to test the hypothesis that increased desialylation of cell surface glycans secondary to hindlimb ischemia (HLI) might help offset the reduction in tissue perfusion that occurs in mouse models of PAD. The utility of the creatine kinase-based (CK6) promoter for restricting gene expression to skeletal muscle was also examined by comparing it to the cytomegalovirus (CMV) promoter after systemic administration following surgically-induced HLI. Despite reduced blood flow to ischemic limbs, CK6 promoter-driven luciferase activities in ischemic gastrocnemius (GA) muscles were ~34-, ~28-, and ~150-fold higher than in fully-perfused contralateral GA, heart, and liver, respectively, 10 days after intravenous administration. Furthermore, luciferase activity from the CK6 promoter in ischemic GA muscles was ~2-fold higher than with CMV, while in the liver CK6-driven activity was ~42-fold lower than with CMV, demonstrating that the specificity of ischemic skeletal muscle transduction can be further improved with muscle-specific promoters. Studies with Evans blue dye and fluorescently-labeled lectins revealed that vascular permeability and desialylation of cell surface glycans were increased in ischemic hindlimbs. Furthermore, AAV9/CK6/Luc vector genome copy numbers were ~6-fold higher in ischemic muscle compared to non-ischemic muscle in the HLI model, whereas this trend was reversed when the same genome was packaged in the AAV-1 capsid (which binds sialylated, as opposed to desialylated glycans), further underscoring the importance of desialylation in the ischemic enhancement of transduction displayed by AAV-9. Taken together, these findings suggest two complementary mechanisms contributing to the preferential transduction of ischemic muscle by AAV-9: increased vascular permeability and desialylation. In conclusion, ischemic muscle is preferentially targeted following systemic administration of AAV-9 in a mouse model of HLI. Unmasking of the primary AAV-9 receptor as a result of ischemia may contribute importantly to this effect.